Identification of “safe harbor” loci in indica rice genome by harnessing the property of zinc-finger nucleases to induce DNA damage and repair - Cantos, Christian; Francisco, Perigio; Trijatmiko, Kurniawan R.; Slamet-Loedin, Inez; Chadha-Mohanty, Prabhjit K. (Frontiers in Plant Science, 2014)
Zinc-finger nucleases (ZFNs) have proved to be successful tools for targeted genome manipulation in several organisms. Their main property is the induction of double-strand breaks (DSBs) at specific sites, which are further repaired through homologous recombination (HR) or non-homologous end joining (NHEJ). However, for the appropriate integration of genes at specific chromosomal locations, proper sites for gene integration need to be identified. These regions, hereby named safe harbor loci, must be localized in non-coding regions and possess high gene expression. In the present study, three different ZFN constructs (pZFN1, pZFN2, pZFN3), harboring β-glucuronidase (GUS) as a reporter gene, were used to identify safe harbor loci regions on rice chromosomes. The constructs were delivered into IR64 rice by using an improved Agrobacterium-mediated transformation protocol, based on the use of immature embryos. Gene expression was measured by histochemical GUS activity and the flanking regions were determined through thermal-asymmetric interlaced polymerase chain reaction (TAIL PCR). Following sequencing, 28 regions were identified as putative sites for safe integration, but only one was localized in a non-coding region and it also possessed high GUS expression. These findings have significant applicability to create crops with new and valuable traits, since the site can be subsequently used to stably introduce one or more genes in a targeted manner.